Identification of Coconut Business Potential with Location Quotient (LQ) in West Muna Regency, Southeast Sulawesi - dhian herdhiansyah (JURNAL AGROINDUSTRI HALAL, 2020)
The potential for developing coconut commodity plantations in Tiworo Islands, West Muna Regency, Southeast Sulawesi has not been utilized. This study aims to (a) identify the form and type and copra business capacity; and (b) find out the potential of a coconut business located in Tiworo District, West Muna Regency, Southeast Sulawesi. Determination of the location of research carried out deliberately (purposive). The method used is a questionnaire and interview. The analysis used is descriptive-analytical and Location Quotient (LQ) analysis. The results showed that the form of coconut business in the District of Tiworo Kepulauan Muna Barat Regency is classified as a micro business with assets of 50 million each with a total income in the copra business having a garden of Rp. 36,733,125. Then the total coconut business income without processing Rp. 6,493,522 and the total copra business income without having a garden is Rp. 43. 226,647. Potential identification based on the Location Quotient (LQ) calculation shows that the average value of the calculation of a coconut business by owning a plantation and a coconut business without processing of 1.1 is included in the base category, meaning that these two coconut businesses are superior coconut businesses. while the coconut business without owning a garden of 0.8 is classified in the Non-base category or has not yet become a leading business so it needs to be developed further so that this business can become a superior business and be able to compete with other businesses that already exist in the district of Tiworo Islands, West Muna Regency Southeast Sulawesi.Keywords: Potential, Coconut Business, analytical descriptive, Location Quotient, West Muna